Analysis Of Stock Waqf Based On The Qur'an Hadith And Waqf Regulations In Indonesia - Herayani, Dini (Zona Law And Public Administration Indonesia, 2024)
Waqf is a form of social worship that establishes a connection between humans and Allah SWT. Throughout Islamic history, among the social institutions in Islam, waqf has played a very important role in developing social, economic, and cultural activities within the Muslim community. Waqf is closely related to enhancing human welfare, which also relates closely to the objectives of Islamic sharia, al-maslahah. One form of waqf that is still widely discussed is waqf shares. The principle of masalih al-mursalah or public interest is the benchmark for allowing waqf shares. The potential of waqf shares is significant in Indonesia, yet it has not been fully optimized due to widespread lack of knowledge among the public regarding the implementation of waqf shares. Therefore, there is a need for in-depth understanding of waqf shares comprehensively